Expression of bcl-2 and p53 proteins in nasopharyngeal carcinoma. Absence of correlation with the presence of EBV encoded EBER1-2 transcripts and latent membrane protein-1. Issue 1 (February 1995) - Kouvidou, Ch; Kanavaros, P; Papaioannou, D; Stathopoulos, E; Sotsiou, F; Datseris, G; Tzardi, M; Kittas, C; Delides, G
Abstract : Aims —To investigate the immunohistochemical expression of bcl-2 and p53 proteins in nasopharyngeal carcinomas in relation to the expression of the Epstein-Barr virus (EBV) encoded EBER messenger RNAs (mRNAs) and latent membrane protein-1 (LMP-1). Methods —Formalin fixed, paraffin wax embedded tissue from 44 nasopharyngeal carcinomas (NPCs) was stained by immunohistochemistry for p53, bcl-2 and LMP-1 proteins and by RNA in situ hybridisation for EBER mRNAs. Results —The tumours were divided histologically into 13 cases of keratinising squamous cell NPC (KNPC), 15 cases of non-keratinising squamous cell NPC (NKNPC) and 16 cases of undifferentiated NPC (UNPC). Bcl-2 expression was observed in five of 15 NKNPC cases and in six of 16 UNPC cases; p53 expression was observed in one of 13 KNPC, two of 15 NKNPC and four of 16 UNPC cases. EBER 1-2 transcripts were detected in five of 15 NKNPC and nine of 16 UNPC cases, while LMP-1 expression was observed in one of 16 UNPC cases. All 13 KNPCs were EBV and bcl-2 negative. No correlation was found between the presence of EBER 1-2 transcripts and the detection of bcl-2 or p53 proteins, or both, in NPC cells. Conclusions —The expression of bcl-2 and p53 proteins may be associated with the level of the tumour cell differentiation in NPC. In addition, in view of the important role of the bcl-2 protein in the inhibition of apoptosis, the expression of bcl-2 protein may contribute to tumour cell survival in a proportion of NPCs. Furthermore, in the light of previous findings that the p53 gene in most UNPCs is in the wild-type configuration, mechanisms other than mutation may be responsible for stabilisation of the p53 protein in UNPCs.